New Generation Cadmium-Free Quantum Dots for Biophotonics and Nanomedicine - Xu, Gaixia; Zeng, Shuwen; Zhang, Butian; Swihart, Mark T; Yong, Ken-Tye; Prasad, Paras N (Chemical reviews, 2016)
This review summarizes recent progress in the design and applications of cadmium-free quantum dots (Cd-free QDs), with an emphasis on their role in biophotonics and nanomedicine. We first present the features of Cd-free QDs and describe the physics and emergent optical properties of various types of Cd-free QDs whose applications are discussed in subsequent sections. Selected specific QD systems are introduced, followed by the preparation of these Cd-free QDs in a form useful for biological applications, including recent advances in achieving high photoluminescence quantum yield (PL QY) and tunability of emission color. Next, we summarize biophotonic applications of Cd-free QDs in optical imaging, photoacoustic imaging, sensing, optical tracking, and photothermal therapy. Research advances in the use of Cd-free QDs for nanomedicine applications are discussed, including drug/gene delivery, protein/peptide delivery, image-guided surgery, diagnostics, and medical devices. The review then considers the pharmacokinetics and biodistribution of Cd-free QDs and summarizes current studies on the in vitro and in vivo toxicity of Cd-free QDs. Finally, we provide perspectives on the overall current status, challenges, and future directions in this field.